Increased Expression of Meteorin-Like Hormone in Type 2 Diabetes and Obesity and Its Association with Irisin - Irina AlKhairi; Preethi Cherian; Mohamed Abu-Farha; Ashraf Al Madhoun; Rasheeba Nizam; Motasem Melhem; Mohamed Jamal; Suleiman Al-Sabah; Hamad Ali; Jaakko Tuomilehto; Fahd Al-Mulla; Jehad Abubaker (Cells, 2019)
Type 2 diabetes (T2D) is a growing pandemic associated with metabolic dysregulation and chronic inflammation. Meteorin-like hormone (METRNL) is an adipomyokine that is linked to T2D. Our objective was to evaluate the changes in METRNL levels in T2D and obesity and assess the association of METRNL levels with irisin. Overall, 228 Arab individuals were enrolled. Plasma levels of METRNL and irisin were assessed using immunoassay. Plasma levels of METRNL and irisin were significantly higher in T2D patients than in non-diabetic patients (p < 0.05). When the population was stratified based on obesity, METRNL and irisin levels were significantly higher in obese than in non-obese individuals (p < 0.05). We found a significant positive correlation between METRNL and irisin (r = 0.233 and p = 0.001). Additionally, METRNL and irisin showed significant correlation with various metabolic biomarkers associated with T2D and Obesity. Our data shows elevated METRNL plasma levels in individuals with T2D, further exacerbated with obesity. Additionally, a strong positive association was observed between METRNL and irisin. Further studies are necessary to examine the role of these proteins in T2D and obesity, against their ethnic background and to understand the mechanistic significance of their possible interplay.